Socio-demographic Characteristics of Delivery by Caesarean Section of the Vietnamese Population: A Cross-sectional study - Rupdi Lumban Siantar; Dewi Rostianingsih; Maslan Pangaribuan; Nguyễn Hoàng Thuỳ Linh; Maretalinia Maretalinia (JURNAL INFO KESEHATAN, 2025)
The rising trend of caesarean deliveries in Vietnam, influenced by various social and demographic factors, has raised public health policy concerns as many procedures are performed without clear medical indications. This study seeks to explore the relationship between socio-demographic factors and the likelihood of caesarean section deliveries within the Vietnamese population. This study employed a cross-sectional design using data from the Vietnam Multiple Indicator Cluster Survey (MICS) 2020–2021, which utilized a two-stage stratified cluster sampling method to ensure national representativeness. The analysis focused on 1,049 women aged 15–49 who had at least one child. Data were collected through standardized questionnaires and analyzed using chi-square tests and binary logistic regression to examine associations between socio-demographic factors and caesarean section deliveries. Based on data from 1,343 Vietnamese women, this study found that 32.84% of deliveries were by caesarean section (CS). Bivariate analysis showed significant associations between CS and factors such as maternal age, education, residence, wealth, and place of delivery. However, multivariate logistic regression revealed that only maternal age, household wealth, and place of delivery remained significant predictors. Older women and those from wealthier households had higher odds of CS, while births at commune health centers were less likely to involve CS. Education level and rural residence were not independently associated with CS after adjustment.